Peningkatan Keterampilan 4C Mahasiswa PAI melalui Model Project Based Learning - Pratama, Rido Awal; Muqowim; Mustaqim, Ali (IIQ An Nur Yogyakarta, 2024)
This research contains the application of the Project Based Learning model as an effort to improve 4C skills, especially students. The problems in this research are the lack of interest in learning, creativity, students' skills in developing thinking abilities and the learning model applied by lecturers is always monotonous using the lecture method. The aim of this research is to explain the process of implementing the Project Based Learning model and analyze the improvement of students' 4C skills. The method used is qualitative with data reduction analysis techniques, data presentation and drawing conclusions. The results of this research explain that implementing the Project Based Learning model can improve students' 4C skills. This is indicated by the assignment of learning videos which can improve critical thinking skills in terms of material selection, location placement and exchanging ideas. Creative in terms of video positioning, video editing, video packaging. Collaborative in terms of working together and respecting each other's opinions. Communicative in terms of discussing by conveying ideas that can maximize the results of the learning video assignment.